Low-cost equipment for electroformation of Giant Unilamellar Vesicles. (October 2018) - Bellon, Javier Alejandro; Pino, Marcelo Javier; Wilke, Natalia
Graphical abstract: Abstract: Giant Unilamellar Vesicles (GUVs) constitute a very useful model for biomembranes. They are usually generated by electroformation using sinusoidal potential waves applied between two platinum electrodes or electrodes composed of glasses covered by indium tin oxide (ITO). Here we present the design of a programmable, compact and low cost wave generator that allows applying different waveforms, even with initial non-periodical shapes. Thus, it allows to optimize the potential waveform for the particular GUV' composition. We also describe the design of a low cost, reusable chamber with stainless steel electrodes that allows using very small volumes of solution (0.3 mL). With this chamber, a larger number of GUVs were generated in less electroformation times compared to ITO electrodes. The general characteristics of the obtained GUVs are comparable to those electroformed in platinum or ITO surfaces. The chamber, combined with the wave generator comprises a simple, reusable, programmable and low cost system for the formation of GUVs.